2023
DOI: 10.34133/plantphenomics.0015
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropy Structures Plant Height and Seed Weight Scaling in Barley despite Long History of Domestication and Breeding Selection

Abstract: Size scaling describes the relative growth rates of different body parts of an organism following a positive correlation. Domestication and crop breeding often target the scaling traits in the opposite directions. The genetic mechanism of the size scaling influencing the pattern of size scaling remains unexplored. Here, we revisited a diverse barley ( Hordeum vulgare L.) panel with genome-wide single-nucleotide polymorphisms (SNPs) profile and the measurement of their plant height and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…These two traits are controlled by several genes and are positively correlated [ 41 ]. He et al [ 45 ] reported eight markers on barley chromosomes 2H and 5H that are associated with plant height and thousand-grain weight.…”
Section: Discussionmentioning
confidence: 99%
“…These two traits are controlled by several genes and are positively correlated [ 41 ]. He et al [ 45 ] reported eight markers on barley chromosomes 2H and 5H that are associated with plant height and thousand-grain weight.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds are concentrated in the 0-5 cm soil depth, and different aboveground community coverage has different ability to capture seeds. The number of plants per unit area gradually increased with the increase of aboveground community coverage, and the ability to capture different types of seeds gradually increased, thus reducing the dominance index of dominant species in the soil seed bank (He et al 2023;Khalaj et al 2023). Compared with the 0-5 cm soil depth seed bank, the trend of dominance index in the two communities is not consistent in the 5-10 cm soil depth, and the dominance index of germination seedlings under medium coverage P. australis community is the lowest.…”
Section: Differences Of Natural and Potential Regeneration Ability Be...mentioning
confidence: 99%
“…Interestingly, larger seeds tend to have less biomass allocation to their coats than expected given their size – that is coat and kernel weights scale allometrically with a slope < 1 (Wu et al ., 2019; Chen et al ., 2020). This suggests that pleiotropy or genetic linkage may pose constraints to the free variation of kernel and coat sizes (He et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%